Enabling Deep Negative Rates to Fight Recessions - Agarwal, R. (Ruchir) (IMF working paper, 2019)
"The experience of the Great Recession and its aftermath revealed that a lower bound on interest rates can be a serious obstacle for fighting recessions. However, the zero lower bound is not a law of nature; it is a policy choice. The central message of this paper is that with readily available tools a central bank can enable deep negative rates whenever needed - thus maintaining the power of monetary policy in the future to end recessions within a short time. This paper demonstrates that a subset of these tools can have a big effect in enabling deep negative rates with administratively small actions on the part of the central bank. To that end, the authors (i) survey approaches to enable deep negative rates discussed in the literature and present new approaches; (ii) establish how a subset of these approaches allows enabling negative rates while remaining at a minimum distance from the current paper currency policy and minimizing the political costs; (iii) discuss why standard transmission mechanisms from interest rates to aggregate demand are likely to remain unchanged in deep negative rate territory; and (iv) present communication tools that central banks can use both now and in the event to facilitate broader political acceptance of negative interest rate policy at the onset of the next serious recession."--Abstract.